LARUTAN UBI JALAR UNGU DAN BUAH BIT SEBAGAI BAHAN IDENTIFIKASI KEBERADAAN PLAK GIGI - Diyah Fatmasari; Supriyana Supriyana; Sukmawati Sukmawati (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2017)
TITLEPurple sweet potatoes and bits as dental plaque identification agentsABSTRACTUse of natural material for substituting chemical agents nowdays as a need. Anthocyanin contain on purple sweet potatoes and betacyanin on bit fruit has potency as a source of natural colour detection to see dental plaque. Purpose of this research to find ability differences of solution purple sweet potatoes dan bit fruit to detect dental plaque. Research design was quasy experimental with post test only design as an approach and quantitative descriptively was used to analyse the data. Sample was 26 students of elementary school who have mixed dentition. Data collection with cross over design. First day the students were applied by solution of purple sweet potatoes and the second they were applied by solution of bit fruit to detect of dental plaque.Research result shown mean score of plaque index after application of purple sweet potatoes was 1.358 and 1.942 after application of bit fruit. Mean of plaque index of bit fruit was higher than compared to mean of plaque index of purple sweet potatoes. This condition as betacyanin as pigmen which contain on bit fruit has good stability when compared with anthocyanin as pigmen on purple sweet potatoes. Bit fruit is a choice of natural material for identification dental plaque. Keywords : purple sweet potatoes, bit fruit, dental plaque, anthocyanin, betacyanin